Tindak Pidana Korupsi Gaji Ganda yang Dilakukan oleh Pegawai Negeri Sipil - Muhammad Anwar Musadad (Bandung Conference Series: Law Studies, 2023)
Abstract. Corruption is a crime that has always been in the spotlight in this country. Corruption in Indonesia is a criminal act that is classified as an extraordinary crime because it has damaged, not only state finances and the country's economic potential, but has also destroyed the pillars of socio-cultural, moral, political and legal security systems for the country. In Article 3 of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption, it is explained that corruption is an act that benefits oneself or another person or a corporation, abuses authority, opportunity or means available to them. because of a position or position that can be detrimental to the State's finances or the State's economy. Corruption can also be done by anyone and anywhere. Holders of power or position in a region are more likely to commit acts of corruption. This is evidenced by the many corruption cases involving the names of state administrators, the majority of whom are Civil Servants (PNS). One of the criminal acts of corruption committed by Civil Servants is the criminal act of double salary corruption in Decision Number 3/Pidsus-Tpk/2020/PN Bna. In this decision, the defendant, who is a civil servant in the Pidie Regency Government, was proven to have committed a criminal act of corruption by receiving a double salary from two government places, namely the Pidie Regency Government and the Aceh Provincial Government. The defendant forged a letter when registering as a Candidate for Civil Servants (CPNS) at the Aceh Provincial Government, and misused study permits from the two agencies in order to get salaries in the two governments. This research method is a normative juridical approach with descriptive analytical research specifications, then the data collection technique is library research, then uses a qualitative analysis method. During the trial, the defendant was charged with committing a criminal act of corruption by violating Article 3 of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption Crimes, but the Panel of Judges Member II conducted a Dissenting Opinion by strengthening its opinion seeing the elements elements of the criminal act that the defendant committed, that it was not true that the defendant was sentenced for violating Article 3 of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption Crimes, instead the defendant was proven to have violated Article 2 paragraph (1) of the Law -Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning Eradication of Corruption Crimes. Abstrak. Korupsi merupakan salah satu tindak pidana yang selalu menjadi sorotan dalam negeri ini. Korupsi di Indonesia merupakan tindak pidana yang tergolong dalam extraordinary crime atau kejahatan luar biasa karena telah merusak, tidak saja keuangan Negara dan potensi ekonomi Negara, tetapi juga telah meluluhkan pilar-pilar sosio budaya, moral, politik, dan tatanan hukum keamanan Negara. Dalam Pasal 3 Undang-Undang Nomor 31 Tahun 1999 jo Undang- Undang Nomor 20 Tahun 2001 tentang Pemberantasan Tindak Pidana Korupsi dijelaskan, bahwa korupsi merupakan perbuatan yang menguntungkan diri sendiri atau orang lain atau suatu korporasi, menyalahgunakan kewenangan, kesempatan, atau sarana yang ada padanya karena kedudukan atau jabatan yang dapat merugikan keuangan Negara atau perekonomian Negara. Korupsi juga dapat dilakukan oleh siapa saja dan dimana saja. Pemegang kekuasaan maupun jabatan suatu daerah lebih cenderung melakukan tindak pidana korupsi. Hal ini dibuktikan dengan banyaknya kasus korupsi yang menyeret nama-nama pejabat penyeenggara negara yang mayoritas adalah Pegawai Negeri Sipil (PNS), komersialisasi jabatan telah menjalar di segala bidang dan dilakukan oleh kalangan atas maupun bawahan. Salah satu tindak pidana korupsi yang dilakukan oleh Pegawai Negeri Sipil adalah tindak pidana korupsi gaji ganda dalam Putusan Nomor 3/Pidsus- Tpk/2020/PN Bna. Dalam putusan tersebut terdakwa yang merupakan seorang Pegawai Negeri Sipil di Pemerintahan Kabupaten Pidie terbukti melakukan tindak pidana korupsi dengan mendapatkan gaji ganda dari dua tempat pemerintahan, yaitu Pemerintahan Kabupaten Pidie dan Pemerintahan Provinsi Aceh. Terdakwa memalsukan surat saat mendaaftarkan diri sebagai Calon Pegawai Negeri Sipil (CPNS) di Pemerintahan Provinsi Aceh, dan menyalahgunakan surat izin belajar dari dua instansi tersebut agar mendapatkan gaji di dua pemerintahan tersebut. Metode penelitian ini ialah pendekatan yuridis normatif dengan spesifikasi penelitian deskriptif analisis, selanjutnya teknik pengumpulan data ialah studi kepustakaan (Library Research), kemudian menggunakan metode analisis secara kualitatif. Dalam persidangan, terdakwa dihukum dengan dakwaan melakukan tindak pidana korupsi dengan melanggar Pasal 3 Undang-Undang Nomor 31 Tahun 1999 jo Undang-Undang Nomor 20 Tahun 2001 tentang Pemberantasan Tindak Pidana Korupsi, namun Majelis Hakim Anggota II melakukan Dissenting Opinion dengan memperkuat pendapatnya melihat unsur-unsur tindak pidana yang terdakwa lakukan, bahwa tidak benar terdakwa dijatuhkan hukuman dengan pelanggaran Pasal 3 Undang-Undang Nomor 31 Tahun 1999 Jo Undang-Undang Nomor 20 Tahun 2001 tentang Pemberantasan Tindak Pidana Korupsi, melainkan terdakwa terbukti melakukan pelanggaran Pasal 2 ayat (1) Undang-Undang Nomor 31 Tahun 1999 jo Undang-Undang Nomor 20 Tahun 2001 tentang Pemberantasan Tindak Pidana Korupsi.